PEMBUATAN KAMUS DIGITAL BILLINGUAL BERBASISI ADOBE FLASH PADA MATERI PUBLIC AREA - Mirza Ismail Akbar, - (2019)
This research is motivated by student's limited ability in knowlage of tools and cleaning materials learning in public area because of media learning ueses that still need an innovation, so it is necessary to make an application that can support student at classroom. The research is intended to make digital bilingual dictionary that can help the student to understand foreign term in tools and cleaning materials' public area. The research uses "Research and Development" method, with PPE model that is Planning, Production, and Evaluation. This step is supported by main software that called Adobe Flash CS5. Assessors of this research consisted of two media validators and a housekeeping teacher. Instruments which use in the research is observation guideline and expert judgement format. The result of research based on interview and observation was showing no learning media that can be public area learning complement that use English term. The application step started from drafting digital billingual dictionary identity, drafting material, flowchart and storyboard. The production process is based on the planning that has been made. The expert judgement's result which is given by media validators and housekeeping teacher are obtained from the digital bilingual dictionary that has been made is in the category of very feasible to use as a support for learning media. Recomendation that can be delivered from the result of this research, it is hoped teacher can use this digital billingual dictionary as learning media inovation, for the researcher can be followed up related to implementation of the digital bilingual dictionary as public area learning media